Extent of exposure to occupational hazards among mason workers in Obio/Akpor Local Government Area in Rivers State - Samuel, Gentle Kitoye; Amechi, Bright Chinwendu (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This research looked at the risks that masons in Rivers State's Obio/Akpor Local Government Area faced on the job. A descriptive survey study approach was used using 2000 masons as the population. Using a multi-stage sampling technique, 440 people made up the sample size. Three specialists verified the validity. A reliability value of 0.85 was assigned to a questionnaire used as the data-gathering tool. At the 0.05 threshold of significance, the obtained data were analyzed using the mean and linear regression. The result showed a high extent of physical hazards (2.60±0.90), biological hazards (2.61±0.95), chemical hazards (3.15±1.42), psychological hazards (2.94±0.92), ergonomic hazards (2.67±1.01), and mechanical hazards (2.72±0.82). It was concluded that masons in Obio/Akpor Local Government Area of Rivers State are exposed to different forms of occupational hazards that affect their health, therefore low extent of safety practice is responsible for the high extent of occupational hazards exposure among masons. It was recommended among others that, the Ministry of Works should upon approval of any construction work, verify and ensure that a stand-by safety personnel is attached to the project and is on the ground every day to enforce safety regulations on site.